Peningkatan Literasi Akuntansi Dan Keuangan Remaja: Mempersiapkan Generasi Cerdas Finansial Di Era Digital [Improving Accounting and Financial Literacy among Adolescents: Preparing a Financially Smart Generation in the Digital Era] - Elfita, Rizki Amalia; Agustina, Heni; Wulan, Tri Deviasari; Ghofirin, Mohamad (Indonesia Berdaya, 2026)
Absdtract. The development of digital financial services or financial technology (fintech) has had a significant impact on the financial behavior of young people. Senior high school students are increasingly exposed to application-based financial services, yet their level of financial literacy remains low. Data from the 2025 National Survey on Financial Literacy and Inclusion (SNLIK) by the Financial Services Authority (OJK) shows that Indonesia’s financial literacy index stands at 66.46%, while the financial inclusion index reaches 80.51%. Among the 15–17 age group, the literacy level is only 51.86%, indicating a wide gap between the utilization of financial services and the understanding of inherent risks. This community service program was carried out at SMAN 1 Bangsal, Mojokerto, with the aim of improving financial literacy and introducing fintech safely to students. The implementation method included needs analysis, interactive workshops, digital financial application simulations, and evaluations through pre-tests and post-tests. The results showed a significant increase in students’ understanding average financial literacy scores improved by 70–100% across various indicators. Students demonstrated wiser attitudes in managing pocket money, recording expenses, and understanding the risks of illegal online loans. This program reinforces previous literature stating that the integration of financial literacy with digital literacy can foster healthy financial behavior. Abstrak. Perkembangan layanan keuangan digital atau financial technology (fintech) membawa dampak signifikan terhadap perilaku finansial generasi muda. Siswa sekolah menengah atas (SMA) semakin terpapar layanan keuangan berbasis aplikasi, namun tingkat literasi keuangan mereka masih rendah. Data Survei Nasional Literasi dan Inklusi Keuangan (SNLIK) OJK 2025 menunjukkan bahwa indeks literasi keuangan masyarakat Indonesia sebesar 66,46%, sementara indeks inklusi keuangan mencapai 80,51%. Pada kelompok usia 15–17 tahun, tingkat literasi hanya 51,86%, menandakan adanya kesenjangan yang lebar antara pemanfaatan layanan keuangan dengan pemahaman risiko yang melekat. Program pengabdian masyarakat ini dilaksanakan di SMAN 1 Bangsal, Mojokerto, dengan tujuan meningkatkan literasi keuangan dan mengenalkan fintech secara aman kepada siswa. Metode pelaksanaan meliputi analisis kebutuhan, workshop interaktif, simulasi aplikasi keuangan digital, serta evaluasi dengan pre-test dan post-test. Hasil menunjukkan peningkatan signifikan pemahaman siswa: nilai rata-rata literasi keuangan meningkat 70–100% pada berbagai indikator. Siswa menunjukkan sikap lebih bijak dalam mengelola uang saku, mencatat pengeluaran, serta memahami risiko pinjaman online ilegal. Program ini memperkuat literatur terdahulu yang menyebutkan bahwa integrasi literasi keuangan dengan literasi digital mampu menciptakan perilaku finansial sehat.